Financial Literacy and Financial Capability - What Is What? - Andrea LUČIĆ; Dajana BARBIĆ; Nikola ERCEG; Irena PALIĆ; Marija UZELAC (Communications of International Proceedings, 2022)
This s review plays a vital role in providing a critical summary and the overview of what is and what is not know in the field related to the terminology of financial literacy and capabiltiy. Even though the research and practice of financial literacy has been vastly growing in the past couple of years, it is left underdeveloped in terms of clear theoretical, conceptual and methodological terms. The paper maps 329 journal articles in the field of financial literacy and financial capability. The conceptual and methodological gaps suggest academics and practitioners should be oriented towards theoretical positioning, the division of appropriate measurement tools, the more usage of qualitative and mixed method approaches and multidisciplinary approach to research.
Keywords: financial literacy; financial capability; systematic literetature review; terminology